Enhanced antibacterial potential of exopolysaccharide-stabilized spice oil emulsions against foodborne pathogens - Singh, Jahnavi Kumari; Djiazet, Steve; Devi, Palanisamy Bruntha; Ghomdim, Horliane Nzali; Reddy, G. Bhanuprakash; Kavitake, Digambar; Shetty, Prathapkumar Halady (Frontiers in Nutrition, 2025)
Exopolysaccharides (EPSs) from lactic acid bacteria (LAB) are known to have diverse applications in food and pharmaceuticals due to their functional properties. Emulsification is one of the important potentials of microbial polysaccharides, revealing its role as a natural emulsifier. In this study, glucan has been explored for emulsification with spice oils from Xylopia aethiopica (Xae), Monodora myristica (Mm), and Fagara lepreuri (Fl) Cameroon underutilized spices. Emulsifying ability, turbidity, emulsion droplet size, and micrographs of glucan-based spice oil emulsion were studied. The effect of sonication has been studied on droplet size and morphology of the emulsions. Sonication treatment has improved the emulsion stability by converting the larger emulsion droplets into smaller ones. The results of the disk diffusion assay confirmed antibacterial activity of emulsions, exhibiting high antibacterial efficiencies against food pathogens Listeria monocytogenes 1143, Shewanella putrefaciens 8104, and Salmonella enterica 950. This study underscores the potential of EPS as a natural emulsifying agent in food preservation, pharmaceuticals, and antimicrobial applications.